Competencies of experienced sustainability professionals - Venn, Ronald; Vandenbussche, Valerie; Perez, Paquita (Frontiers in Sustainability, 2024)
This paper presents an empirical study on key competencies of experienced sustainability professionals. We use an elaborate action research approach to collect and analyze qualitive data from sustainability professionals in Belgium (Wallonia). The iterative action-reflection process included a written assignment, an interactive workshop, qualitative data analyses, focus-group discussions, and the corroboration of findings through participant feedback. The 18 participating sustainability professionals had on average 24 years of work experience out of which 17 years in the field of sustainability. Our analysis provides strong empirical evidence for the existence of Sustainability Intervention Competencies which is a cluster of six key competencies, namely interpersonal collaboration competency, capacity building competency, intrapreneurial competency, strategic competency, political competency, and implementation competency. Together with a set of basic sustainability competencies they enable the profound analysis and understanding of sustainability issues, the co-creation of innovative solutions, and the facilitation of transition processes toward a sustainable future. Furthermore, we present empirical evidence for an integrated learning competency which binds two complementary forms of knowledge together, namely topical knowledge and lived experience. This study contributes to the newly forming empirical research stream on competencies of sustainability professionals in Sustainability Science. We outline implications for Human Resource Management as well as Higher Education and Vocational Training.